APPLICATION OF SELF DIRECTED LEARNING TO REDUCE MATHEMATICS ACADEMIC PROCRASTINATION - Siregar, Rahma; Nasution, Ja’far (ALGORITMA: Journal of Mathematics Education, 2024)
Self Directed Learning is a learning process of self-will and self-control so that it can solve problems or tasks. This study examines the differences in academic procrastination in mathematics learning in groups that apply Self Directed Learning learning models and groups that use conventional learning models. This type of research is a quasi-experiment. The instrument of this research is an academic procrastination questionnaire given to 25 students in the control class and 26 students in the experimental class. This study's results indicate no significant difference in reducing mathematics academic procrastination in students who apply Self Directed Learning with students who apply conventional learning at SMP N 4 Padangsidimpuan. However, regarding the average value, there is a difference in reducing mathematics academic procrastination in students who apply Self Directed Learning with students who apply conventional learning at SMP N 4 Padangsidimpuan. So, classes with self-directed learning are better than classes with conventional learning.